Weightlifting exercises enhance athletic performance that requires high-load speed strength - Hori, N.; Newton, R. U.; Nosaka, K.; Stone, M. H. (Strength and Conditioning Journal, 2005)
Weightlifting exercises can be effective for enhancing athletic performance. This article provides a biomechanical and physiological discussion as to why weightlifting exercises are useful to improve athletic performance and how they may be integrated into a training program.